2010
DOI: 10.1002/elan.200880006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Shewanella oneidensis MR‐1 Outer Surface Structures in Extracellular Electron Transfer

Abstract: The ability of the metal reducer Shewanella oneidensis MR-1 to generate electricity in microbial fuel cells (MFCs) depends on the activity of a predicted type IV prepilin peptidase; PilD. Analysis of an S. oneidensis MR-1 pilD mutant indicated that it was deficient in pili production (Msh and type IV) and type II secretion (T2S). The requirement for T2S in metal reduction has been previously identified, but the role of pili remains largely unexplored. To define the role of type IV or Msh pili in electron trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 50 publications
5
71
0
1
Order By: Relevance
“…We confirmed that deletion of the gene encoding PilD (pilD), a predicted prepilin peptidase, also resulted in a comparable reduction with omcA/mtrC (Fig. 10) analysis of cell extracts of strain pilD has demonstrated that PilD is involved in the processing of type IV, Msh, and T2S prepilin proteins, and this strain is also reported to lack OMCs, including OmcA and MtrC (Bouhenni et al, 2010). Our electrochemical comparisons among WT, omcA/mtrC, and pilD cells clearly indicate that OmcA and MtrC function as the major reductases for EET from attached cells to electrode surfaces (i.e., DET reaction).…”
Section: In-frame Deletion Mutants Of Om C-cytssupporting
confidence: 71%
See 1 more Smart Citation
“…We confirmed that deletion of the gene encoding PilD (pilD), a predicted prepilin peptidase, also resulted in a comparable reduction with omcA/mtrC (Fig. 10) analysis of cell extracts of strain pilD has demonstrated that PilD is involved in the processing of type IV, Msh, and T2S prepilin proteins, and this strain is also reported to lack OMCs, including OmcA and MtrC (Bouhenni et al, 2010). Our electrochemical comparisons among WT, omcA/mtrC, and pilD cells clearly indicate that OmcA and MtrC function as the major reductases for EET from attached cells to electrode surfaces (i.e., DET reaction).…”
Section: In-frame Deletion Mutants Of Om C-cytssupporting
confidence: 71%
“…It should be noted that the E m of 50 mV detected for intact MR-1 cells is a markedly more positive potential compared to those reported for purified OM c-Cyts (170 mV for MtrC and 210 mV for OmcA) (Eggleston et al, 2008;Firer-Sherwood et al, 2008;Hartshorne et al, 2009). In addition to OM c-Cyts, MR-1 cells are known to synthesize several flavin and quinone derivatives that function as electron shuttles, a few of which strongly bind to the outer cell surface and provide redox signals characteristic of immobilized electroactive species (Saffarini et al, 2002;Okamoto et al, 2009;Bouhenni et al, 2010). Therefore, the large difference in E m between purified OM c-Cyts and intact cells has led many researchers to speculate that the observed redox wave at 50 mV is attributable to cell-attached menaquinone, whose midpoint potential is approximately 80 mV (Li et al, 2010;Zhao et al, 2010), rather than OM c-Cyts.…”
Section: Whole-microorganism Voltammetrymentioning
confidence: 99%
“…To date, many exoelectrogens have been employed in MFCs, including Shewanella putrefaciens (Kim et al, 1999), Geobacter sulfurreducens (G. sulfurreducens) (Bond and Lovley, 2003), Rhodoferax ferrireducens (Chaudhuri and Lovley, 2003), Klebsiella pneumoniae (K. pneumoniae) (Zhang et al, 2008), etc. These exoelectrogens, which are all cultivated in MFCs under neutral pH conditions, primarily depend on four mechanisms of electron transfer from fuels to electrodes, including membrane-bound cytochromes (Bond and Lovley, 2003;Bouhenni et al, 2010;Zhang et al, 2008), conductive bacterial pili (Gorby et al, 2006;Reguera et al, 2006), oxidation of reduced secondary metabolites (Zhuang et al, 2010a) or soluble redox mediators (Bond and Lovley, 2005;Rabaey et al, 2004;Wang et al, 2007). Furthermore, previous literatures have proved that flavin (Marsili et al, 2008), 2-amino-3-carboxy-1,4-naphthoquinon (Freguia et al, 2009) and 2,6-di-tert-butyl-p-benzoquinone (Deng et al, 2010) could be excreted by Pseudomonas aeruginosa (P. aeruginosa), Lactococcus lactis, K. pneumoniae, respectively, facilitating electron transfer in MFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Extended periplasmic and outer membranes S. oneidensis possess three different types of extracellular proteinaceous appendages: (1) Msh pili, (2) TFP and (3) flagella (Bouhenni et al, 2010), but it was not clear which one of these acts as MNWs. Msh pili have been shown to be necessary for extracellular electron transfer (Fitzgerald et al, 2012), while TFP and flagella have been shown to be dispensable (Bouhenni et al, 2010).…”
Section: Pilimentioning
confidence: 99%
“…Msh pili have been shown to be necessary for extracellular electron transfer (Fitzgerald et al, 2012), while TFP and flagella have been shown to be dispensable (Bouhenni et al, 2010). However, MNWs in S. oneidensis are made up of outer membrane vesicle chains which subsequently elongate and become MNWs ( Fig.…”
Section: Pilimentioning
confidence: 99%